Clinical Efficacy Of Ayurvedic Interventions In Nabothian Cyst: A Case Report - Lata, Suman; Tiwari, Satyendra Kumar (Journal of Neonatal Surgery, 2025)
A Nabothian cyst is a benign mucous-filled cyst that develops on the cervix, often discovered incidentally during routine ultrasonography. Studies indicate that approximately 12% of women may have Nabothian cysts, with prevalence varying widely. These cysts are usually asymptomatic, but in some cases, they may be associated with lower abdominal pain, irregular menstrual cycles, and excessive white discharge.A 48-year-old female patient visited the Panchakarma O.P.D at Govt. Ayurvedic College & Hospital, Patna (Bihar), presenting with complaints of lower abdominal pain, irregular menstrual cycles, and heavy white discharge for the past two months. A USG report revealed a mildly bulky uterus with multiple Nabothian cysts in the uterine cervix, with an endometrial thickness of 10.9 mm.The patient underwent conservative Ayurvedic treatment for one month, including: Chandraprabha Vati, Kanchanar Guggulu, Pushyanuga Churna, Arogyavardhani Vati, Tab Asthiposhak, Dashmoolarista After one month of treatment, a follow-up USG showed a normal cervix with no cysts, indicating the effectiveness of Ayurvedic management in resolving Nabothian cysts without complications. This case highlights how Ayurvedic formulations can provide effective, non-invasive treatment for Nabothian cysts, promoting reproductive health and menstrual regularity